Access, knowledge and experience with fluorodeoxyglucose positron emission tomography/computed tomography in infection management: a survey of Australia and New Zealand infectious diseases physicians and microbiologists. Issue 5 (13th May 2019) - Douglas, Abby P.; Thursky, Karin A.; Worth, Leon J.; Harrison, Simon J.; Hicks, Rodney J.; Slavin, Monica A.
Abstract: Background: Despite fluorodeoxyglucose positron emission tomography/computed tomography (FDG‐PET/CT) being funded only for staging and restaging of some malignancies in Australia, there is evidence of benefit of FDG‐PET/CT for infection indications such as pyrexia of unknown origin (PUO), prolonged neutropenic fever (NF) and prosthetic device infection. Aim: To evaluate the current knowledge, utilisation of and gaps in access to FDG‐PET/CT for infectious indications by Australasian infectious diseases (ID) physicians and microbiologists. Methods: An online survey was administered to ID and microbiology doctors practising in adult medicine in Australia and New Zealand through two established email networks. Using targeted questions and case‐based examples, multiple themes were explored, including access to FDG‐PET/CT, use and perceived benefit of FDG‐PET/CT in diagnosis and monitoring of non‐malignant conditions such as NF and PUO, and barriers to clinical use of FDG‐PET/CT. Results: A response was received from 120 participants across all states and territories. Onsite and offsite FDG‐PET/CT access was 63% and 31% respectively. Eighty‐six percent reported using FDG‐PET/CT for one or more infection indications and all had found it clinically useful, with common indications being PUO, prosthetic device infections and use in the immunocompromised host for prolonged NF and invasive fungal infection. Thirty‐eight percent reported barriers in accessing FDG‐PET/CT for infection indications and 76% would utilise FDG‐PET/CT more frequently if funding existed for infection indications. Conclusion: Access to FDG‐PET/CT in Australia and New Zealand is modest and is limited by lack of reimbursement for infection indications. There is discrepancy between recognised ID indications for FDG‐PET/CT and funded indications.